Avaliação da influência de extratos brutos vegetais submetidos à infestação de Sitophilus zeamais (coleóptera; curculionidae), em milho armazenado - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This research deals with the importance and damage caused by stored grain pests. The study instrument was Sitophilus zeamais, a primary pest of great relevance in the agronomic context, as it causes a series of qualitative and quantitative damage. The aim of this study is to evaluate the influence of crude Amazonian plant extracts on corn weevil under storage conditions. The Amazon region is known for being the nursery of different species that are used in the cosmetic, food and pharmaceutical industries. Many of the species are only used empirically, making it necessary to carry out further studies on their secondary chemical and metabolic compounds with potential for the production of bioinsecticides. Corn is part of the range of cereals with the greatest agricultural and industrial potential in the grain purchase and sale sector. This is due to its nutritional value, high adaptability to different climatic conditions and its versatility of use, this being a source of human and animal food, the cosmetics industry and even used in high-tech industries for the manufacture of ethanol. Recently, pest resistance to insecticides is a widely discussed issue, thus highlighting the need for biological control methods aimed at minimizing pest infestation, in addition to the environmental issue and the preservation of human and animal health. During the period of the experiment, the repellency and attractiveness of the crude plant extract of the species Astronium lecointei Ducke, Aniba canelilla (H.B.K) Mez and Carapa guianensis on the infestation of stored grain pests was evaluated. The results are relevant, which reinforces the need for more detailed research on the plant materials used, since in the tests with plant extract from the leaves of Aniba canelilla (H.B.K) Mez and crude plant extract of Carapa guianensis, no live insects were found.
Keywords: Grãos armazenados; Sitophilus zeamais; Extrato bruto vegetal; Astronium lecointei Ducke; CNPQ:: CIÊNCIAS AGRÁRIAS